A Commentary on Althusser's 1963 Presentation of Bourdieu and Passeron. (December 2019) - Branchu, Charlotte; Robbins, Derek
The commentary provides contextual information about the seminar which Bourdieu and Passeron gave in the École Normale Supérieure on 6 December 1963. It appears that the intended series of seminars was curtailed, perhaps because the initial seminar of 6 December exposed the extent to which Althusser was formally managing the intentions of his guest speakers and resisting the implications of their ongoing research on students and their studies. The commentary argues that the conflict between Althusser and Bourdieu/Passeron was inter-generational in that Althusser's attitudes had been shaped by his experience as a victim of Nazi oppression whereas those of Bourdieu/Passeron were defined, instead, by their unwilling participation in the French colonial oppression of indigenous Algerians. Althusser was intent on examining philosophically the validity of various contemporary versions of social science whereas Bourdieu and Passeron were engaged in educational research which was scrutinizing sociologically the validity of precisely this supposedly detached philosophical perspective. In short, the commentary is aligned with the Bourdieu/Passeron position in that it seeks to offer an historical sociology of the encounter of December 1963.